An Empirical Job-Search Model, with a Test of the Constant Reservation-Wage Hypothesis - Kiefer, Nicholas M.; Neumann, George R. (Journal of Political Economy, 1979)
This paper provides an empirically tractable version of a job-search model. The model is estimated using data on a sample of workers who were laid off when their plants closed. A generalization of the empirical model which allows for reservation wages to change over duration of unemployment is provided and estimated. Reservation wages are found to decline significantly with duration. Applications of the model and the estimates to explain diverse labor market phenomena are provided.